Religion, culture and mental health - Loewenthal, Kate Miriam (Cambridge University Press, 2006)
"Are religious practices involving seeing visions and speaking in tongues beneficial or detrimental to mental health? Do some cultures express distress in bodily form because they lack the linguistic categories to express distress psychologically? Do some religions encourage clinical levels of obsessional behaviour? And are religious people happier than others? By merging the growing information on religion and mental health with that on culture and mental health, Kate Loewenthal enables fresh perspectives on these questions. This book deals with different psychiatric conditions such as schizophrenia, manic disorders, depression, anxiety, somatization and dissociation as well as positive states of mind, and analyses the religious and cultural influences on each."--Jacket